2022
DOI: 10.3390/agronomy12123215
|View full text |Cite
|
Sign up to set email alerts
|

Applied Selenium as a Powerful Antioxidant to Mitigate the Harmful Effects of Salinity Stress in Snap Bean Seedlings

Abstract: Selenium (Se) plays several significant roles in regulating growth, development and plant responses to various abiotic stresses. However, its influence on sulfate transporters (SULTRS) and achieving the harmony with other salt-tolerance features is still limited in the previous literatures. This study elucidated the effect of Se supplementation (5, 10 and 20 µM) on salt-stressed (50 mM NaCl) snap bean seedlings. Generally, the results indicated that Se had dual effects on the salt stressed seedlings according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 83 publications
1
7
0
Order By: Relevance
“…3C and Table 5). A similar pattern of results was obtained, by Saidmuradi et al [93] where they found that salinity stress reduced K + uptake by plants, but maintaining adequate K + levels in plants mitigated adverse effects of salinity [94,95]. Under salinity stress condition, the content of Na + in leaves decreased by application of Kh (HA) treatments and their combination which also led to increased K + content in leaves, [3], (Fig.…”
Section: Nutrient Uptake and Availability By Barley Plantssupporting
confidence: 80%
“…3C and Table 5). A similar pattern of results was obtained, by Saidmuradi et al [93] where they found that salinity stress reduced K + uptake by plants, but maintaining adequate K + levels in plants mitigated adverse effects of salinity [94,95]. Under salinity stress condition, the content of Na + in leaves decreased by application of Kh (HA) treatments and their combination which also led to increased K + content in leaves, [3], (Fig.…”
Section: Nutrient Uptake and Availability By Barley Plantssupporting
confidence: 80%
“…In line with our findings, Zhang et al (2021b) highlighted that MT enhanced the growth of sugar beet, i.e., leaf area, fresh and dry weights in addition to increasing chlorophyll content under salinity stress. These responses may be due to decreased ROS generation (caused by salinity stress) and MDA accumulation as well as increased antioxidant enzyme activities in stressed plants (Han et al, 2017;Farag et al, 2022;El-Beltagi et al, 2023b) and intensive ROS accumulation sites in chloroplasts caused by the imbalance between electron transport rates and СО 2 fixation. Generation of ROS leads to protein degradation and pigment bleaching.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it inhibits the activity of enzymes, which results in chlorophyll degradation and photosynthetic inhibition (Fatma et al, 2016). The visible harmful impacts of salinity include decreases of leaf area, necrosis and abscission (Fariduddin et al, 2019). Additionally, salt stress has a considerable effect on the ion uptake of essential nutrients and causes impaired growth promotion, thus resulting in obstacles to normal growth and development (Elkelish et al, 2019;Alnusairi, 2021;Youssef et al, 2021;El-Taher et al, 2022;Abdelkader et al, 2023aAbdelkader et al, , 2023b.…”
Section: Introductionmentioning
confidence: 99%
“…Saidimoradi et al [ 38 ] obtained a similar pattern of results, finding that salinity stress reduced the uptake of K + by strawberry plants. Maintaining adequate K + levels in plants could mitigate adverse salinity conditions [ 11 , 81 , 82 ]. Under the saline condition, our results show that Na + content in leaves was decreased, whereas Kh and SA treatments and their combination increased K + content ( Figure 4 C,D).…”
Section: Discussionmentioning
confidence: 99%